Implementation of The Scramble Learning Model to Improve Student Learning Outcomes in Christian Religion Education Subjects - Sibulo, Deviana; Sapus, Debi Afliana (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
The purpose of this study was to determine student learning mastery by applying the scramble learning model in Christian Religious Education learning at the Evangelical Christian Church of Timor Manulai I Elementary School. The type of research used in this study was Classroom Action Research. The results showed that learning using the scramble method could improve student learning outcomes in the subject of Christian Religious Education and ethics which was marked by an increase in student learning outcomes in each cycle. Student learning outcomes in cycle I reached 70.83% which achieved the Minimum Completeness Criteria and increased in Cycle II to 85.33% of students. Student learning outcomes increased from the average score of Pre-Cycle students by 72.41%, increased in cycle I by 70.83% and learning outcomes in Cycle II increased by 85.33%.